Em busca da autonomia operacional do Banco Central do Brasil como instrumento de estabilização da moeda - Matta, Leandro Amaral (2003)
Central Banks have as first mission to be the guard of the money power, in order to guarantee fmances stability of their countries. From that premise, it will be demonstrated how much The Brazil Central Bank (BACEN) needs to get autonomy, in order to accomplish its mission, which has a specialy technical nature. Even the question about to set an autonomous BACEN does not be pacific, in terms of consensus, we shall try to expose that model advantages, as an important way to monetary stability. In Brazil, besides BACEN have a lot of functions, it is submitted to the govemment, and many times there are pressures, because sometimes govemment plans, being to be realized at short time, are not so compatible with monetary stability, principally when an actuation at long t~rm is needed. The autonomy we commend to BACEN does not mean absolute independence, however. It will get the responsibility to allow the right marks adopted by the govemment, and will must to render account about its actuation, that must be absolutely transparent. In order to do what it must do, BACEN need be given administrative, budgetary and operational autonomy. Df course BACEN powers will me limited by legal barriers. When detaching the autonomy of the BACEN, we bring tona a pertinent factor to the question that is inflation. ProcessoAo is about one to detach the autonomy ofthe BACEN, brings tona a pertinent factor to the question that is inflation. One is about a process is very bad, because it destroys gradually the Economy, and when that becomes to be chronic, as in Brazil till 90ths years, that causes instability, disturbing administrative pIanning, unless those realized at very short time. The need to get over controI the inflationary process that occurred in last decades, in many countries, lead to some changes and setting a monetary politics based in Inflation Targeting. In those countries where Inflation Targeting was adopted, at same time occurred also an increase in Central Banks independence. The more autonomy they have, the more credibility the get. Countries that turned theirs Central Banks autonomous got more success to get over inflation controI, as Chile, New Zeeland, which Bank controI is the most rigidity. Gennany also adopted that system, and the twelve countries that compose the Europe Union too. If we need an efficient BACEN, by assuring it can be able to accomplish their functions, it is fundamental it has given budgetary, administrative and operational autonomy. It means it needs to rule the 192 article ofthe Federal Constitution, through a Complement Law. When BACEN have assured by Iaw the autonomy it needs, there will be a valuable way to put inflation over controI, and in consequence, Brazil may get stability, in order to promote a development in right time, by an strategic planning at long terms.